Novel insight into etiology, diagnosis and management of primary adrenal insufficiency - Malikova, Jana; Flück, Christa E (Hormone research in paediatrics, 2014)
Primary adrenal insufficiency (PAI) is a rare condition in childhood which is either inherited (mostly) or acquired. It is characterized by glucocorticoid and maybe mineralocorticoid deficiency. The most common form in children is 21-hydroxylase deficiency, which belongs to the steroid biosynthetic defects causing PAI. Newer forms of complex defects of steroid biosynthesis are P450 oxidoreductase deficiency and (apparent) cortisone reductase deficiency. Other forms of PAI include metabolic disorders, autoimmune disorders and adrenal dysgenesis, e.g. the IMAGe syndrome, for which the underlying genetic defect has been recently identified. Newer work has also expanded the genetic causes underlying isolated, familial glucocorticoid deficiency (FGD). Mild mutations of CYP11A1 or StAR have been identified in patients with FGD. MCM4 mutations were found in a variant of FGD in an Irish travelling community manifesting with PAI, short stature, microcephaly and recurrent infections. Finally, mutations in genes involved in the detoxification of reactive oxygen species were identified in patients with unsolved FGD. Most mutations were found in the enzyme nicotinamide nucleotide transhydrogenase, which uses the mitochondrial proton pump gradient to produce NADPH. NADPH is essential in maintaining high levels of reduced forms of antioxidant enzymes for the reduction of hydrogen peroxide. Similarly, mutations in the gene for TXNRD2 involved in this system were found in FGD patients, suggesting that the adrenal cortex is particularly susceptible to oxidative stress.
Keywords: hirzutismus; Steroids; 46, XX Disorders of Sex Development; kojenec; Glucocorticoids; Infant; glukokortikoidy; dítě; Adrenal Insufficiency; Child; steroidy; Child, Preschool; adrenální insuficience; Humans; předškolní dítě; 11-beta-hydroxysteroiddehydrogenasy; 11-beta-Hydroxysteroid Dehydrogenases; vrozené poruchy metabolismu steroidů; poruchy sexuálního vývoje s karyotypem 46, XX; Hirsutism; Steroid Metabolism, Inborn Errors; lidé